Eucholoeops ameghino, 1887 (Xenarthra, tardigrada, megalonychidae) from the santa cruz formation, argentine patagonia: Implications for the systematics of santacrucian sloths - De Iuliis, Gerardo (2014)
New well-preserved remains of the megalonychid sloth Eucholoeops Ameghino, 1887 recovered under strict stratigraphic control from late Early Miocene Santa Cruz Formation (c. 19 to 14 Ma; Santacrucian Age), together with analysis of older collections, consideration of intraspecific variation in extinct and extant sloths, and assessment of the validity of the early literature on Santacrucian sloths, permit revision of the status of the numerous species erected for this genus. The current contribution deals with the systematics of E. ingens Ameghino, 1887, but its methodology provides a basis for revision of other Eucholoeops species, as well as other sloth genera recovered from the Santa Cruz Formation. The failure to make progress on the systematics of the Santacrucian taxa since their first description is shown to be due mainly to a combination of the poor quality of many of the specimens, which are often fragmented and incomplete and from older collections, as well as inadequate stratigraphic and geographic control of their recovery, an overly rigid reliance on the early literature that accompanied their descriptions, and lack of consideration for intraspecific variation. A neotype is designated for E. ingens, as the original specimen is no longer available. The species E. latirostris Ameghino, 1891, E. externus Ameghino, 1891, and E. curtus Ameghino, 1894 are considered as junior synonyms of E. ingens.